Reconstituting Orders after Neo-liberalism? - The “Growth Fetish”, Gender and Environment in Sino-European Interchanges - Petersen, Hanne (Kvinder, Køn & Forskning, 2015)
This article seeks to bring together aspects regarding issues of gender, legal pluralism, ecofeminism, sustainability, and globalization. I have been inspired by increasing interaction with interdisciplinary researchers in Denmark and China working on gender dynamics in a globalized and Asianized world, as well as by an interest in art as a source of understanding and expressing communal norms, values and conflicts. The article reflects upon the links between the high value of economic growth in both regions and art and artistic installations, which express increasing concern about the consequences of growth, amongst other things for economic inequality and sustainability. Linking and assembling such critical concerns, practices and expressions might be a way of approaching a reconstitution of global and local orders, including ambivalent and uncertain gender orders in the near future.